Constipation in pregnancy: causes and remedies - Zahoor, Sana; Babar, Masroor Ellahi; Javed, Muhammad Mohsin; Hussain, Tanveer (Progress in Nutrition, 2018)
Constipation is a common gastrointestinal complaint in pregnancy that occurs in about 11-40% of the women. It is described by symptoms like pain, distress, straining, hard lumpy stools and a sense of incomplete bowel evacuation. Diet rich in fiber and increased fluid intake is recommended to improve defecation. The use of laxatives and probiotics is also reported to alleviate constipation, though the safety and efficacy of laxatives and probiotics on the mother and fetus need to be established. This review article provides an insight on different factors leading to constipation in pregnancy and evaluation of different remedies used for the treatment of constipation in pregnancy.